2016
DOI: 10.1039/c6ra08285h
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatical analysis and preliminary study of the role of lipase in lipid metabolism in Mucor circinelloides

Abstract: The filamentous fungus Mucor circinelloides has been widely used as a model organism to investigate the mechanisms of lipid accumulation. Although a lot of work has been done to analyze and explore many of the essential enzymes/genes related to lipid accumulation in M. circinelloides, the function of lipase in this fungus has not been studied at all. In this study, we report some important characteristics of all 30 lipases, and especially 4 lipases Lip6, Lip10, Lip19 and Lip24 with functional analyses in Mucor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…Total RNA of S. cerevisiae was extracted using TRIzol reagent after grinding under liquid N 2 (Zan et al . ) and reverse‐transcribed using the Prime Script RT reagent kit (Takara) according to the manufacturer's instructions. About 2 μ g of total RNA was reverse‐transcribed to cDNA by PrimeScript1st strand cDNA Synthesis Kit (Takara).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA of S. cerevisiae was extracted using TRIzol reagent after grinding under liquid N 2 (Zan et al . ) and reverse‐transcribed using the Prime Script RT reagent kit (Takara) according to the manufacturer's instructions. About 2 μ g of total RNA was reverse‐transcribed to cDNA by PrimeScript1st strand cDNA Synthesis Kit (Takara).…”
Section: Methodsmentioning
confidence: 99%
“…Media and growth conditions for M. circinelloides have been previously described in our previous study. 29,30,32 Lipase genes were overexpressed in the M. circinelloides uridine auxotroph pleu-MU402. 33 This strain could grow at 30 °C in YPG media containing 3 g/L yeast extract, 10 g/L tryptone, 20 g/L glucose, and 200 μg/mL uridine at pH 4.5.…”
Section: Methodsmentioning
confidence: 99%
“…However, the model of Cdk1/Cdc28-dependent activation of the lipase activity of Tgl4p is a good reference to study the molecular mechanism balancing catabolic and anabolic activities of multifunctional lipases. Previous studies from our group showed that the lipidproducing fungus M. circinelloides lipases Lip6 and Lip10 harbored both a typical lipase catalytic site motif GXSXG and an acyltransferase signature motif H-(X) 4 -D. 29,30 Overexpression of either lipase Lip6 or Lip10 promoted cell growth and increased lipid production. 30 These results suggested that Lip6 or Lip10 may function both as an acyltransferase and a lipase in M. circinelloides.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…M. circinelloides grows well in culture-containing triacylglycerol, indicating a potential source of extracellular lipases [ 89 ]. Many scientific studies from a hereditary perspective have ascertained that M. circinelloides produces many lipase genes [ 35 , 46 , 91 ] .…”
Section: Metabolism Of Tagmentioning
confidence: 99%